Fragmentasi Layanan dan Determinan Sosial: Analisis Kualitatif Kegagalan Discharge Planning dan Rekomendasi Model Kolaboratif Lintas Sektor (Sehati) - Yohana Teodosia Setu; Saverinus Suhardin; Imakulata Bete; Awaliyah Muslimah Suwetty; Moses Filmon Nennogasu; Adhytrio Yohanes Nubatonis (Universitas Malahayati, 2026)
ABSTRACT High readmission rates among Patients with Mental Disorders (ODGJ) are often linked to Discharge Planning (DP) failures. This study aims to deeply explore systemic barriers and the need for community-based solutions to prevent DP from functioning as an effective Transitional Care (TC) mechanism at Naimata Mental Hospital, Kupang. This descriptive phenomenological qualitative research involved 14 key participants (Mental Hospital Health Personnel, Community Health Center Nurses, ODGJ Patients, and Families/Caregivers) through In-depth Interviews. Data were analyzed using thematic methods to identify major barriers in the post-discharge continuum of care. Eight main themes were found, which include: (1) Massive handoff failure, manifested as